Impact of MaxZero™ needle-free connector on the incidence of central venous catheter-related infections in surgical intensive care unit. Issue 2 (March 2019) - Clavier, Thomas; Ferguen, Mathias; Gouin, Philippe; Gillibert, André; Dusenne, Mikaël; Merle, Véronique; Veber, Benoit
Abstract: Background: Central venous catheter-related infections (CRIs) are a complication of central venous catheters in intensive care unit (ICU). Some needle-free connectors have been designed to decrease CRI, but there is a lack of data concerning their impact on infection. Objectives: The objective was to explore the impact of MaxZero™ connectors (BD; Franklin Lakes, US) on CRI in ICU. Methods: Observational, pre–post design study (2011–2013 and 2014–2016) conducted in the surgical ICU of a tertiary care hospital (18 beds). Patients with a central venous catheter and a length of stay ≥48 h were included. The connectors replaced all disposable caps used on infusion stopcocks and ramps. The primary parameter was to compare the incidence of CRI between the "before" period and the "after" period. Results: A total of 1633 patients were included (789 "before" and 844 "after"). There was no difference between groups concerning the global duration of catheterisation (12.5 ± 11.5 days vs. 12.1 ± 10.9 days). There were 61 CRIs before and 28 CRIs after the introduction of connectors; the incidence of CRI in the "before" group was 20.33 CRI/year (6.18 CRI per 1000 catheter-days) vs. 9.33 CRI/year (2.73 CRI per 1000 catheter-days) in the "after" group (incidence rate ratio = 0.44; 95% confidence interval = 0.28–0.68, p < 0.001). However, after a global analysis of the 6-year period, when adjusting for seasonal effect and pre-existing linear trend, the effect was no longer significant (adjusted incidence rate ratio = 0.57; 95% confidence interval = 0.24–1.35, p = 0.20). Conclusions: Our results do not allow us to conclude to a potential beneficial effect of MaxZero™ on CRI but are compatible with its prolonged and safe use in ICU. Only future prospective works will be able to confirm the value of these connectors for CRI prevention.